2015
DOI: 10.17556/jef.08506
|View full text |Cite
|
Sign up to set email alerts
|

Laboratuar Uygulamalarını Farklı Şekillerde Raporlaştırmanın Kavramsal Anlamaya ve Modsal Betimleme Kullanımına Etkisi

Abstract: ÖzetBu çalışmada; laboratuar uygulamalarını raporlaştırırken argümantasyon tabanlı bilim öğrenme (ATBÖ) ve geleneksel rapor formatlarını kullanmanın, öğren-cilerin kimyasal tepkimelerde hız ve denge konularıyla ilgili kavramları öğrenme düzeylerine ve modsal betimlemeleri kullanma durumlarına etkisi incelenmiştir. Çalışma, 2013-2014 yılı bahar döneminde Türkiye'deki bir devlet üniversitesinin Fen Bilgisi Öğretmenliği Anabilim Dalı'nda öğrenim görmekte olan ve Genel Kimya Laboratuarı II dersini alan 38 öğrenci … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Günel (2009) states that the use of non-traditional writing activities in laboratories, unlike traditional laboratory reports, is an approach that allows the production of cognitive and metacognitive activities. On the other hand, Aslan & Tekin (2015) found that reporting of laboratory practices differently did not make a difference between the learning levels of control and experimental group students in their study. Meriç (2003) argued that the use of the V diagram would be more effective than writing a traditional report.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Günel (2009) states that the use of non-traditional writing activities in laboratories, unlike traditional laboratory reports, is an approach that allows the production of cognitive and metacognitive activities. On the other hand, Aslan & Tekin (2015) found that reporting of laboratory practices differently did not make a difference between the learning levels of control and experimental group students in their study. Meriç (2003) argued that the use of the V diagram would be more effective than writing a traditional report.…”
Section: Introductionmentioning
confidence: 77%
“…The most commonly used writing activity in undergraduate level laboratory applications is the activity of generating a laboratory report writing. The laboratory reports are usually written in the form of a traditional report (Aslan & Tekin, 2015). The laboratory reports are the most frequently used writing types in primary school, middle school, high school, and higher education institutions as well as at the undergraduate level.…”
Section: Introductionmentioning
confidence: 99%
“…The scientific process skills are the basic skills which make learning in science easy, bring in research ways and methods, and enable the students to be active, develop their sense of taking responsibility of their own learning and increase the permanence of learning (Çepni, Ayas, Johnson & Turgut, 1997). While science is being learnt, speaking and writing, mathematics, images like pictures, graphics and diagrams, devices like experiment and measurement tools and activities aimed to practice are needed (Aslan & Tekin, 2015). Glynn and Muth (1994), remark that the writing activities are related to the scientific process skills and the learning of the students.…”
Section: Introductionmentioning
confidence: 99%